Pengaruh Biaya Lingkungan Terhadap Kinerja KeuanganPerusahaan (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2017-2021) - Lydia Gustina Putri (UNIVED Press, 2023)
This study aims to examine the effect of applying environtment cost to the company's financial performance. The research sample is manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The number of research samples is 40 manufacturing companies. Data analysis uses linear regression analysis. The results showed that the application of environtment cost in the form of environmental costs which were proxied by ROA and ROE variables had a positive effect on financial performance. This means that environmental cost variables are in line with stakeholder theory, that is, stakeholders will get broader and more complete information about the company's activities so that the information presented is free from information asymmetry